2012
DOI: 10.1021/la3003146
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Latex Colloids at Rough Mineral Surfaces: An Analogue Study Using Nanopatterned Surfaces

Abstract: Deposition of latex colloids on a structured silicon surface was investigated. The surface with well-defined roughness and topography pattern served as an analogue for rough mineral surfaces with half-pores in the submicrometer size. The silicon topography consists of a regular pit pattern (pit diameter = 400 nm, pit spacing = 400 nm, pit depth = 100 nm). Effects of hydrodynamics and colloidal interactions in transport and deposition dynamics of a colloidal suspension were investigated in a parallel plate flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 56 publications
(127 reference statements)
0
6
0
Order By: Relevance
“…Not surprisingly, when r roughness > r critical , media surface roughness enhances particle deposition, as has been widely reported. 19,22,44,45 In contrast, when r roughness < r critical , media surface roughness contributes to decreased particle deposition, relative to smooth surfaces; this may explain some reported outcomes as well. 19,21,22 To explore the applicability and validate the efficacy of the proposed framework for describing particle deposition on surfaces in response to variable media surface roughness, the framework was applied to data reported by Vanhaecke et al (1990) (upper left inset in Figure 4(b)), who systemically investigated the kinetics of Pseudomonas aeruginosa attachment on stainless steel with several levels of surface roughness.…”
Section: ■ Materials and Methodsmentioning
confidence: 98%
“…Not surprisingly, when r roughness > r critical , media surface roughness enhances particle deposition, as has been widely reported. 19,22,44,45 In contrast, when r roughness < r critical , media surface roughness contributes to decreased particle deposition, relative to smooth surfaces; this may explain some reported outcomes as well. 19,21,22 To explore the applicability and validate the efficacy of the proposed framework for describing particle deposition on surfaces in response to variable media surface roughness, the framework was applied to data reported by Vanhaecke et al (1990) (upper left inset in Figure 4(b)), who systemically investigated the kinetics of Pseudomonas aeruginosa attachment on stainless steel with several levels of surface roughness.…”
Section: ■ Materials and Methodsmentioning
confidence: 98%
“…For example, Chen et al (2010) coated stainless steel and aluminum alloys with zeolite to increase deposition surface roughness and increased colloid deposition by up to 50% 19 . Darbha et al (2010) reported a positive correlation between calcite surface roughness and the number of attached colloidal particles 20 ; they also found that surface roughness-enhanced particle deposition was more significant for smaller particles (0.3 μm), as compared to larger (2 μm) ones 21 . Zan et al (2008) investigated opportunities for enhancing orthopaedic stainless steel affinity to host tissue and also found that more colloidal particles attached on rough deposition surfaces than on smooth ones 22 .…”
mentioning
confidence: 99%
“…Surface roughness is proportional to the specific surface area of porous media. Higher surface roughness and specific surface area increases the active attachment sites to capture pathogens and inhibits their migration ( Morales et al, 2009 , Krishna Darbha et al, 2012 , Torkzaban and Bradford, 2016 ). For instance, crude biochar has rougher surface with the specific surface area 5 orders of magnitude larger than sand, resulting in a significantly stronger adsorption of Escherichia coli through biochar (log removal of 2.32) than sand (log removal of 0.29) ( Mohanty et al, 2014 ).…”
Section: Environmental Geochemical and Hydrological Variablesmentioning
confidence: 99%